Childbearing across Partnerships in Finland and Germany - Jalovaara Marika; Kreyenfeld Michaela (Springer, 2022)
Abstract This chapter examines gender differences in “multipartner fertility” – i.e., having children with several partners – in Germany and Finland. The analyses focus on women and men born around 1970 who are followed until age 41. We show that multipartner fertility is more common in Finland than in Germany. However, there are large East-West differences within Germany. East Germans are less likely to have a second or third child than West Germans, but those East Germans who progress to a higher order birth often have this child with a new partner. We also find some gender differences in behaviour. Men display lower transition rates than women of having a second child with a new partner. Further, having a first child at an early age is strongly and positively associated with multipartner fertility. No consistent relationship between education and multipartner fertility was found for Germany. In Finland, however, low education is associated with elevated risks of having children with different partners.
Divorce in Europe - New Insights in Trends, Causes and Consequences of Relation Break-ups